2018
DOI: 10.3390/vaccines6040079
|View full text |Cite
|
Sign up to set email alerts
|

Does the Immunocompetent Status of Cancer Patients Have an Impact on Therapeutic DC Vaccination Strategies?

Abstract: Although different types of therapeutic vaccines against established cancerous lesions in various indications have been developed since the 1990s, their clinical benefit is still very limited. This observed lack of effectiveness in cancer eradication may be partially due to the often deficient immunocompetent status of cancer patients, which may facilitate tumor development by different mechanisms, including immune evasion. The most frequently used cellular vehicle in clinical trials are dendritic cells (DCs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 236 publications
(332 reference statements)
0
4
0
Order By: Relevance
“…Despite encouraging preclinical and clinical responses, DC-based vaccines still present only a modest clinical outcome. The limited performance can be explained by several mechanisms such as intrinsic factors related to patients (age, prior treatments, genetics…), the source of DCs, vaccination schedule, route of administration or different protocols used to generate vaccines [33] , [42] . A crucial aspect is constituted by DC’s phenotype and their ability to both induce a fully developed immune response (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite encouraging preclinical and clinical responses, DC-based vaccines still present only a modest clinical outcome. The limited performance can be explained by several mechanisms such as intrinsic factors related to patients (age, prior treatments, genetics…), the source of DCs, vaccination schedule, route of administration or different protocols used to generate vaccines [33] , [42] . A crucial aspect is constituted by DC’s phenotype and their ability to both induce a fully developed immune response (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in checkpoint immunotherapy, it was observed that PDL1 status of patients correlates strongly with the observed efficacy and is routinely used as a biomarker to predict efficacy [ 6 ]. In a similar approach, the immunocompetent status of the patient has been studied and found to influence cell-based vaccination therapy as described in the review by Lluesma et al in this issue [ 7 ]. Viral vector based vaccines may suffer from antibody-mediated anti-vector immune responses that impede the therapeutic outcomes.…”
Section: Immune Status Of Individual Patients Impact the Therapeutmentioning
confidence: 99%
“…The authors comment that further research in understanding the development of BDCA1+CD14+ cells is necessary to determine specific targets and improve the efficacy of dendritic-cell based vaccines. In addition, the earlier-mentioned review by Lluesma et al dissects how observed ineffectiveness in anticancer responses is dictated by the immunocompetent status of cancer patients, supporting progression of cancer via mechanisms like immune evasion [ 7 ]. The authors argue that most of the trials apply DC vaccines to patients with an advanced gynecological or breast cancer, which may be a factor mediating low response rates in clinical settings.…”
Section: Immune Status Of Individual Patients Impact the Therapeutmentioning
confidence: 99%
“…Instead, for maturation, a much wider variety of cytokine cocktails have been used by different groups [10]. In particular, a cocktail mixture containing tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and prostaglandin E 2 (PGE2), is currently considered the gold standard for DC maturation and had been largely used in the context of anti-cancer therapeutic vaccines [19,20]. This mix is able to efficiently induce expression of common DC surface maturation markers, uniform DC maturation, as well as high levels of T cell proliferation and priming [19].…”
Section: Introductionmentioning
confidence: 99%